Sustainable entrepreneurial intention among livestock farmers: The role of green entrepreneurial mindset, green entrepreneurial self-efficacy, and environmental awareness - Sari, Ayu Intan; Saputro, Ida Nugroho; Purnomo, Sutrisno Hadi; Rahayu, Endang Tri; Emawati, Shanti (Faculty of Animal Science, Universitas Gadjah Mada, 2025)
Sustainable entrepreneurship plays an important role in driving economic growth while addressing environmental and social challenges as part of efforts to realize sustainable development. Sustainable entrepreneurs are motivated by their intention to solve sustainability issues through an entrepreneurial approach. In this context, this study aims to explore the role of green entrepreneurial mindset, green entrepreneurial self-efficacy, and environmental awareness on the cultivation of sustainable entrepreneurial intention among livestock farmers. This study uses a quantitative approach with a survey method of 280 young entrepreneurial respondents in the livestock sector who are interested in sustainable entrepreneurship. Data were collected using a closed questionnaire with a 5-point Likert scale and analyzed using Structural Equation Modeling (SEM) with the help of SmartPLS software. The study findings reveal that a green entrepreneurial mindset has a positive and significant direct and indirect effect on sustainable entrepreneurial intention through green entrepreneurial self-efficacy and environmental awareness. In addition, green entrepreneurial self-efficacy and environmental awareness have a positive and significant effect on sustainable entrepreneurial intention. This study makes an important contribution to understanding how green entrepreneurial mindset, green entrepreneurial self-efficacy, and environmental awareness can drive sustainable entrepreneurial intention in the livestock sector. In addition, the results of this study emphasize the need for an environmentally conscious entrepreneurial approach in managing livestock businesses.